OTORITAS JASA KEUANGAN - Difa Dini Asfari (Bina Ekonomi, 2014)
Financial system is a network consisting of units of financial institution. In financial institutions there are banking institutions and non-bank financial institutions. Financial institutions have space for each activity. An institution may act as a regulator that regulates the activities of the banking sector or supervisors who supervise banking activities. Regulators and supervisors who are at a certain entity called the financial system authority or OJK (Otoritas Jasa Keuangan). Three authority models developed according to financial market development are the three pillars model that evolved into a twin peaks model and the latter being a model of a single authority. Indonesia is one country that introduced a single authority model in the financial services authority